"Fungating" tumour? No, it's bacterial!. Issue 2 (25th February 2019) - Balakrishnan, Malathy; Phan, Yih Chyn; McIlroy, Brendan; Leung, Edmund
Abstract : A fit and healthy 26-year-old woman presented to the general surgical team with epigastric pain and weight loss of 2 stones over 6 months. She has also a positive family history of ulcerative colitis. As her oesophagogastroduodenoscopy and colonoscopy were normal, a contrasted CT was requested, and it detected an inflammatory mass with fat streaking around her transverse colon. An intrauterine contraceptive device (IUCD) was noted. In light of the CT findings, she underwent a diagnostic laparoscopy. As the inflammatory mass was not separable from the transverse colon, a segmental transverse colectomy was proceeded. The histology revealed multiple actinomycosis abscesses in the mesentery. Subsequently, we learnt that her IUCD had been in situ for the last 7 years, and the source of actinomycosis abscesses is likely from her IUCD. The patient was recommended to have the coil removed and commenced on a 6 months course of amoxicillin.